Supplementary data set corresponding to the manuscript "Can management sustainably improve the productivity of grazed grasslands?" (ASDE-D-24-01382) [Conjunto de datos] - Gandara, Luis; Pereira, Maria Mercedes; Ferrari Usandizaga, Silvana Consuelo (Estación Experimental Agropecuaria Corrientes, INTA, 2025)
This table contains information regarding the evolution of the botanical composition of a subtropical grassland under grazing management that fits the pasture growth curve. Four treatments were compared: high grazing intensity without (T1) and with (T2) clump mowing, and low grazing intensity without (T3) and with (T4) clump mowing. These treatments were repeated at two adjacent sites in the "El Sombrero" locality in Corrientes, Argentina, at approximately 27° 40’01’’S, 58° 47’11’’W. The information includes the INTECO index that describes the dynamics of the change in species cover (winter, summer, straw), dead material, and bare soil;  development of total forage biomass, by species and by family; frequency and abundance (in cover) by species and by family.